2017
DOI: 10.1111/head.13130
|View full text |Cite
|
Sign up to set email alerts
|

Using Search Engines to Investigate Shared Migraine Experiences

Abstract: Objectives To investigate migraine patterns in the United States using Google search data and utilize this information to better understand societal-level trends. Additionally, we aimed to evaluate time-series relationships between migraines and social factors. Background Extensive research has been done on clinical factors associated with migraines, yet population-level social factors have not been widely explored. Migraine internet search data may provide insight into migraine trends beyond information tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Other studies conducted in a pediatric population living in the United States support this annual distribution of consultations, which has been linked to school stressors 10–12 . A similar distribution of interest was described in a study of migraine‐associated internet searches in the United States 13 . The repetitive pattern of decreasing search volumes in December and summer with peaks around February and fall was present throughout the 12 years of that study.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Other studies conducted in a pediatric population living in the United States support this annual distribution of consultations, which has been linked to school stressors 10–12 . A similar distribution of interest was described in a study of migraine‐associated internet searches in the United States 13 . The repetitive pattern of decreasing search volumes in December and summer with peaks around February and fall was present throughout the 12 years of that study.…”
Section: Discussionsupporting
confidence: 64%
“…[10][11][12] A similar distribution of interest was described in a study of migraineassociated internet searches in the United States. 13 The repetitive pattern of decreasing search volumes in December and summer with peaks around February and fall was present throughout the 12 years of that study. The circadian rhythmicity of EM attacks is well-established, but this temporal association less so.…”
Section: Re Sultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Globally, Google is the most popular search engine [16], and search engine queries may reflect the actual problems experienced by Web users. The Internet traffic of Google users can be analyzed using Google Trends (GT), which has been used to investigate user interest in Headache [17,18], Toothache [19], and foot and ankle pain [20]. However, to our knowledge, no study has compared the global user interest in pain-related information using Google.…”
Section: Introductionmentioning
confidence: 99%
“…tweets about migraine activity). 7,8,13,14 Such behavioral characteristics and their sentimental profiles could in return help guide clinical researchers making clinical decisions or improving the quality of care at the population level. A previous study showed that migraine patients actively shared their experience via Twitter and that it was a powerful data source for research.…”
Section: Introductionmentioning
confidence: 99%